Stereoselective synthesis of spiro-beta-lactams using D-(+)-glucose derived chiral pool: remarkable influence of the torquoelectronic effect - Chincholkar, Pinak M.; Puranik, Vedavati G.; Deshmukh, A. R. A. S. (Tetrahedron, 2007)
Diastereoselective synthesis of spiro-beta-lactams via [2+2] cycloaddition reaction of imines and chiral ketenes is described. The chiral ketene was prepared from commercially available, inexpensive D-glucose. Although, theoretically four diastereomers are possible, the reaction yielded only two diastereomers stereoselectively in good to moderate yields. The stereochemical outcome of the reaction was in accordance with the torquoelectronic model. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: imines; ketenes; spiro-beta-lactams; Staudinger reaction; stereoselective synthesis